Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\frac{x-6}{7}+\frac{x-7}{8}+\frac{x-8}{9}=\frac{x-9}{10}+\frac{x-10}{11}+\frac{x-11}{12}\)
=> \(\left(\frac{x-6}{7}+1\right)+\left(\frac{x-7}{8}+1\right)+\left(\frac{x-8}{9}+1\right)=\left(\frac{x-9}{10}+1\right)+\left(\frac{x-10}{11}+1\right)+\left(\frac{x-11}{12}+1\right)\)
=> \(\frac{x+1}{7}+\frac{x+1}{8}+\frac{x+1}{9}-\frac{x+1}{10}-\frac{x+1}{11}+\frac{x+1}{12}=0\)
=> \(\left(x+1\right)\left(\frac{1}{7}+\frac{1}{8}+\frac{1}{9}-\frac{1}{10}-\frac{1}{11}-\frac{1}{12}\right)=0\)
=> x + 1 = 0
=> x = -1
b) \(\frac{x-1}{2020}+\frac{x-2}{2019}-\frac{x-3}{2018}=\frac{x-4}{2017}\)
=> \(\left(\frac{x-1}{2020}-1\right)+\left(\frac{x-2}{2019}-1\right)-\left(\frac{x-3}{2018}-1\right)=\left(\frac{x-4}{2017}-1\right)\)
=> \(\frac{x-2021}{2020}+\frac{x-2021}{2019}-\frac{x-2021}{2018}=\frac{x-2021}{2017}\)
=> \(\left(x-2021\right)\left(\frac{1}{2020}+\frac{1}{2019}-\frac{1}{2018}-\frac{1}{2017}\right)=0\)
=> x - 2021 = 0
=> x = 2021
c) \(\left(\frac{3}{4}x+3\right)-\left(\frac{2}{3}x-4\right)-\left(\frac{1}{6}x+1\right)=\left(\frac{1}{3}x+4\right)-\left(\frac{1}{3}x-3\right)\)
=> \(\frac{3}{4}x+3-\frac{2}{3}x+4-\frac{1}{6}x-1=\frac{1}{3}x+4-\frac{1}{3}x+3\)
=> \(-\frac{1}{12}x+6=7\)
=> \(-\frac{1}{12}x=1\)
=> x = -12
A=1+(2-3-3+5)+(6-7-8+9)+....+(98-99-100+101)+102
=1+0+0+....+102=103
b) |1-2x|>7
=> 1-2x>7 hoặc 1-2x<-7
=> 2x<-6 hoặc 2x>8
=> x<-3 hoặc x>4
\(\frac{5}{6}x+\frac{1}{2}-\frac{1}{3}x=0.75x-\frac{7}{8}\)
\(\frac{5}{6}x-\frac{1}{3}x-\frac{3}{4}x=-\frac{7}{8}-\frac{1}{2}\) ( 3/4x là 0,75x nha)
\(x\times\left(\frac{10}{12}-\frac{4}{12}-\frac{9}{12}\right)=-\frac{7}{8}-\frac{4}{8}\)
\(x\times\left(-\frac{3}{12}\right)=-\frac{11}{8}\Rightarrow x=\frac{11}{8}\div\left(-\frac{3}{12}\right)=-\frac{11}{2}\)
a)72x+72x.49=2450
72x.50=2450
72x=2450:50=49
72x=72
2x=2
x=1
b)(33:11)x=81
3x=81
3x=34
x=4
c)1/6=2/3:8x
8x=2/3:1/6
8x=4
x=1/2
d)(x+1)3=64
(x+1)3=43
x+1=4
x=3
minh chỉ lam đc vậy thôi nha !hi hi
Lời giải:
$(7x-12)+(8x-10)+(3x-14)=4$
$(7x+8x+3x)-(12+10+14)=4$
$18x-36=4$
$18x=40$
$x=\frac{20}{9}$
\(7x-12+8x-10+3x-14-4=0\)
\(18x-40=0\)
\(x=\dfrac{40}{18}=\dfrac{20}{9}\)